Molecular mechanism of acetylated distarch phosphate with pea protein isolate to improve the gel quality of myofibrillar protein gel - Wenting Jiang; Jiulin Wu; Fujia Yang; Xu Chen; Meizhen Chen; Jianlian Huang; Jinhong Wu; Shuo Wan; Xixi Cai; Shaoyun Wang (Food Frontiers)
Abstract It is crucial to improve the gel properties of myofibrillar protein (MP) in the production of surimi products. This study investigated the effects of combining acetylated distarch phosphate (ADSP) with pea protein isolate (PPI) as exogenous additives on the physicochemical properties of Larimichthys crocea MP gel and elucidated the molecular mechanisms underlying the improvement of MP gel quality. The results showed that the mixture of 3% ADSP and 1% PPI increased the MP gel strength to 2.1 times and water holding capacity to 1.8 times. The rheological properties during thermal‐induced gelation were improved, and the surface roughness of gel microstructure was reduced. The protein conformation was stabilized by enhancing surface hydrophobicity and sulfhydryl content, and the gels showed trends of decreasing α‐helix and increasing random coils. Correlation and cluster analysis showed that physicochemical properties of MP gels were closely related to the changes of protein structure and the denaturation of active groups. The molecular interaction between ADSP, PPI, and MP and the mechanism of enhancing the properties and functions of MP gel were further clarified. These findings highlight the feasibility of ADSP–PPI as an effective strategy to improve the quality of fish MP gel.